(untitled) (Hà Nội, 2010)
The publication analyzes the sample data of the 2009 Population and Housing Census on the imbalances of the Sex Ratio at Birth (SRB) in Viet Nam. It provides detailed analysis of the data on the level, trends, regional and demographic variations of the SRB across Viet Nam. It also provides three simulations of how the SRB may evolve in the future, and briefly discusses the policy implications that these may have. This document is designed for a target audience of policy makers, managers, professionals, and researchers. It is hoped by wide dissemination of this document that understanding and awareness will be raised about the critical nature of SRB in overall development planning in Viet Nam.
Keywords: Population,Sex ratio,Tỷ số giới tính,Dân số; Economic aspects,Khía cạnh kinh tế; Vietnam,Vietnam,Việt Nam,Việt Nam